1996
DOI: 10.1093/oxfordjournals.jbchem.a021313
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Role of Glutathione Peroxidase in Apoptosis Induced by Reactive Oxygen Species

Abstract: Selenium-dependent glutathione peroxidase (GPx) plays a protective role in oxidative stress-induced apoptosis. In this study, we demonstrated that MDBK cells, a bovine renal epithelial cell line, exhibited internucleosomal DNA fragmentation characteristic of apoptotic cell death under selenium-deficient conditions with lower doses of hydrogen peroxide (H2O2) than under selenium-supplemented ones. This was due to a decreased amount of GPx in the cells under selenium-deficient conditions, because other antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
1
3

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(83 citation statements)
references
References 0 publications
1
78
1
3
Order By: Relevance
“…GPX1 whose preferred substrate is hydrogen peroxide is the most abundant isoform found in the cytoplasm of nearly all mammalian tissues whereas GPX2 is an intestinal and extracellular enzyme. 82 GPX1 and GPX2 have been reported to protect against apoptosis induced by oxidative stress 83,84 ischemia/reperfusion injury 85 and doxorubicin 86 and to reduce pro-apoptotic Bax expression. 87 GPX4 (also known as phospholipid hydroperoxide glutathione peroxidase, PHGPX) overexpression has been reported to protect against oxidative stress-induced apoptosis.…”
Section: Figure 1 Apoptotic Signaling Pathways (See Text For Further mentioning
confidence: 99%
“…GPX1 whose preferred substrate is hydrogen peroxide is the most abundant isoform found in the cytoplasm of nearly all mammalian tissues whereas GPX2 is an intestinal and extracellular enzyme. 82 GPX1 and GPX2 have been reported to protect against apoptosis induced by oxidative stress 83,84 ischemia/reperfusion injury 85 and doxorubicin 86 and to reduce pro-apoptotic Bax expression. 87 GPX4 (also known as phospholipid hydroperoxide glutathione peroxidase, PHGPX) overexpression has been reported to protect against oxidative stress-induced apoptosis.…”
Section: Figure 1 Apoptotic Signaling Pathways (See Text For Further mentioning
confidence: 99%
“…However, since in cultured hepatocytes the reexpression of subunit P1 is inhibited by dimethyl sulfoxide (38), this suggests a possible correlation between the expression and IL-1 induction of subunit P1 and its high glutathione peroxidase activity. Moreover, it was demonstrated that in cells treated with IL-1 for 24 h, there was a marked increase in the intracellular content of hydroperoxides (40). As a result of an increased exposure to reactive oxygen species after IL-1 treatment, cultured hepatocytes could respond by increasing their glutathione peroxidase activity.…”
Section: Figmentioning
confidence: 99%
“…Apoptotic death of vascular cells results from transduction of death signals triggered by various exogenous stimuli including (a) cytokines, eg, tumor necrosis factor-␣ (TNF␣) (Geng et al, 1996;Robaye et al, 1991); (b) Fas/Fas ligand signaling (Kagi et al, 1994;Nagata, 1997); (c) loss of extracellular matrix (ECM) contacts (anoikis) (Bates et al, 1994;Frisch and Francis, 1994;Re et al, 1994;Ruoslahti and Reed, 1994); (d) hypoxia (Stempien-Otero et al, 1999) and reactive oxygen species (Kayanoki et al, 1996;Li et al, 1997); and (e) withdrawal of a trophic factor, eg, bFGF (Fox and Shanley, 1996) or VEGF (Benjamin et al, 1999;Benjamin and Keshet, 1997). Cytokines released by glioma cells (Zagzag, 1995), eg, TNF-␣ (Geng et al, 1998;Robaye et al, 1991) and TGF-␤ (Pollman et al, 1996), are able to cause apoptosis of endothelial and smooth muscle cells.…”
Section: Tumor-vascular Cell Contact Appears To Be Crucial In Inducinmentioning
confidence: 99%